Social comparison relationship with self-love in adolescents and the implications of guidance and counselling - Rully, Miranda Firdika; Harahap, Ade Chita Putri; Rusman, Abdul Aziz (Universitas Islam Negeri Raden Intan Lampung, 2023)
Confidence is one of the keys to someone being able to perform optimally in everything he does. Reaching that level of self-confidence requires maximum self-management. The purpose of this study was to find out how much social comparison affection is on self-love in adolescents at SMA Negeri 1 Bandar Khalipah. In this study, quantitative research methods and data analysis techniques used simple linear regression. The population of this study were 120 class XI students of SMA Negeri 1 Bandar Khalipah. The sampling technique used random sampling. The sample in this study was 120. The results of this study showed a relationship between social comparison and adolescent self-love, besides that, there was a significant relationship between perception and students' attitudes towards guidance and counselling with students' interest in utilizing guidance and counselling services.